Reducing aeration and cavitation effect in shock absorbers using uid-structure interaction simulation - Czop, Piotr; Gniłka, Jacek (Computer Assisted Methods in Engineering and Science, 2016)
This paper presents a fluid-structure interaction simulation applicable for evaluating and optimizing hydraulic valve designs. A special emphasis is placed on shim stack valve commonly used in automotive and railway shock absorbers. For simplicity, the problem was effectively reduced to a two-dimensional (2D) problem. This was accomplished by introducing section-lines along which the pressure profile was computed to find and evaluate the global minimum. The global minimum was then treated as the design ranking measure. This ranking function provided a means to choose an optimal design from a set of available design variants. In the presented results, the ranking is problem-specific as it identifies and localizes low pressure zones that are the root causes of both aeration and cavitation effects. The damping force performance was experimentally evaluated for both the baseline and optimized valve design using a shock absorber level test on a servo-hydraulic test rig.